Systematic review of instruments aimed at evaluating the severity of bronchiolitis (2020)
Objective: No recent studies have performed a systematic review of all available instruments aimed at evaluating the severity of bronchiolitis. The objective of the present study was to perform a systematic review of instruments aimed at evaluating the severity of bronchiolitis and to evaluate their measurement properties. Methods: A systematic search of the literature was performed in order to identify studies in which an instrument for evaluating the severity of bronchiolitis was described. Instruments were evaluated based on their reliability, validity, utility, endorsement frequency, restrictions in range, comprehension, and lack of ambiguity. Results: A total of 77 articles, describing a total of 32 different instruments were included in the review. The number of items included in the instruments ranged from 2 to 26. Upon analyzing their content, respiratory rate turned out to be the most frequently used item (in 26/32, 81.3% of the instruments), followed by wheezing (in 25/32, 78.1% of the instruments). In 18 (56.3%) instruments, there was a report of at least one of their measurement properties, mainly reliability and utility. Taking into consideration the information contained in the instruments, as well as their measurement properties, one was considered to be the best one available. Conclusions: Among the 32 instruments aimed at evaluating the severity of bronchiolitis that were identified and systematically examined, one was considered to be the best one available. However, there is an urgent need to develop better instruments and to validate them in a more comprehensive and proper way.